2022
DOI: 10.3390/plants11070883
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Longevity and Infectivity of Cucumber green mottle mosaic virus in Soils of the Northern Territory, Australia

Abstract: Cucumber green mottle mosaic virus (CGMMV) is a Tobamovirus of economic importance affecting cucurbit crops and Asian cucurbit vegetables. CGMMV was detected in the Northern Territory (NT) in September 2014, the first record for Australia, with 26 properties confirmed as of May 2016. Research was undertaken to determine virus longevity in soils in the NT and investigate the use of disinfectants to remove viable CGMMV from the soil. An in-field trial at 12 months post-quarantine at four properties, and bioassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Establishment of CGMMV after introduction can lead to further spread by farm machinery, grafting tools, seed trays, clothes, shoes and hands [ 8 , 59 , 60 ]. Dispersal of CGMMV can continue with subsequent planting in soils contaminated with virus-positive plant debris [ 59 , 61 ] and irrigation systems, such as drip and flow irrigation [ 59 ]. Movement of virus-positive fresh produce and associated contaminated surfaces can introduce inoculum into post-harvest settings and, in turn, back into production areas.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of CGMMV after introduction can lead to further spread by farm machinery, grafting tools, seed trays, clothes, shoes and hands [ 8 , 59 , 60 ]. Dispersal of CGMMV can continue with subsequent planting in soils contaminated with virus-positive plant debris [ 59 , 61 ] and irrigation systems, such as drip and flow irrigation [ 59 ]. Movement of virus-positive fresh produce and associated contaminated surfaces can introduce inoculum into post-harvest settings and, in turn, back into production areas.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional RT-PCRs were performed using a Veriti Thermal Cycler (ThermoFisher Scientific, Waltham, MA, USA), utilising Superscript III One Step with Platinum Taq (ThermoFisher Scientific, Waltham, MA, USA), following the manufacturers guidelines. The conditions used in this study can be found in a recent publication from the author [ 14 ], and the primers used were: Coat Protein (CP) (496 bp) [ 15 ] Forward primer, 5′-GATGGCTTACAATCCGATCAC-3′ and Reverse primer, 5′-CCCTCGAAACTAAGCTTTCG-3′; Movement Protein (MP) (809 bp) [ 16 ] Forward primer, 5′-TAAGTTTGCTAGGTGTGATC-3′ and Reverse primer, 5′-ACATAGATGTCTCTAAGTAAG-3′; CGMMV RNA helicase subunit (1053 bp) [ 17 ] Forward primer, 5′-ATGGCAAACATTAATGAACAAAT-3′ and Reverse primer, 5′-AACCACACAGAAAACGTGGC-3′.…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR was performed on a Rotor-Gene 6000 (Qiagen, Hilden, Germany) with SensiFAST TM SYBR ® No-ROX One-Step Kit (Bioline Pty Ltd., Taunton, MA, USA) following the manufacturer’s conditions. The conditions used in this study can be found in a recent publication from the author [ 14 ]; the primers used were: Forward primer, 5′-GTGGTTTCTGGTGTATGGAACGTA-3′, Reverse primer, 5′-CGGGAGCTGAAAATTTGCATATAGT-3′, and probe (RZ_CGMMVmp-03), 5′-[FAM]CACCCCTACAGGATTC[NFQMGB]-3′ [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…TMV remained infective in buried root debris for at least 13 months (Broadbent et al, 1965; Broadbent, 1976). The cucurbit-infecting tobamovirus cucumber green mottle mosaic virus (CGMMV) remained infective in soil for 17 months after the removal of infected watermelon plants (Lovelock et al, 2022). In addition, overwintered soil contaminated with CGMMV-infected plant debris remained infective in bottle gourd propagation (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%